A Learning Based Hierarchial Model to Improve the Performance and Power Consumption in Cloud Computing Environment - Neeshu Sharma, Jasmeen Gill, Gajinderpal Singh (International Journal of Control and Automation, 2020)
Due to high scalability and cost effective infrastructure ,cloud computing is being used for running high performance computing ,enterprise and web applications. Cloud computing has become is one of the emerging field because of rapid increase in IT devices which add on a lot of load to cloud services and the need is to satisfy the demands of users within this limited load .This is the reason many of the researchers are currently exploring this field. In this work we attempt to balance the resource allocation to cloud in a way to minimize energy usage and to decrease overall load in cloud for this A hierarchical based frame work is proposed to ensure better resource allocation to server as well as power management. A Deep Learning based on Reinforcement learning is used to solve the Problem and to balance the resources in a better way.